Positive emotions and quality of life among methadone maintenance therapy patients and their psychosocial correlates / N. Sankari Ganesh - N. Sankari, Ganesh (2017)
Positive emotions and Quality of Life among Methadone Maintenance Therapy patients and their psychosocial correlates Objective: The main objective of this study is to assess the positive emotions and the quality of life among patients on methadone maintenance therapy in Hospital Tuanku Jaa’far, Seremban and University Malaya Medical Centre as well as their associated factors such as their psychosocial correlates. Methodology: This is a cross sectional study, involving 154 patients, which was conducted from March 2017 until May 2017. All patients receiving MMT from both University Malaya Medical Centre and Hospital Tuanku Jaa’far were invited to participate. The sociodemographic and clinical data were obtained from those patients who consented to the study. The Positive Emotion Rating Scale (PERS) and World Health Organization Quality of Life (WHOQOL) BREF were used as instruments. Results: The mean age was 43.8 ±9 years with the most number of the patients being male (97.4%) and Malays (75.3%). Slightly more than half (50.6%) scored above 30 in their Positive Emotion Rating Scale. There was a significant association between the Malay (p=0.042) and, Chinese (p=0.004) ethnic groups with the positive emotions. Marital status (p=0.010) and employment (p=0.008) were also significantly associated with the positive emotions, with being married and employed having higher mean scores. After controlling for potential confounding factors, having positive emotions predicted a better quality of life in all the domains of quality of life. Non diabetic patients also significantly predicted a better quality of life in the overall general health domain where- else being non married and patients without family history of mental illness significantly predicted a lower quality of life in psychological domain and overall quality of life respectively. vii Conclusion: The presence of positive emotions significantly improves the quality of life among patients on MMT program. Other significant contributing factors to the quality of life of these group of patients are being non diabetic, married and not having a positive family history of mental illness. Therefore, attention for including evaluation and teaching of positive emotions during the MMT program should be incorporated for a more holistic treatment approach which extends beyond maintaining abstinence of drug use.